"The reality of knowledge management processes (Knowledge Discovery, Knowledge Storage, Knowledge Sharing, Knowledge Utilization) at King Saud University "A Survey Study - Al Dakheel, Haifa Mansour; Al Qarni, Samaya Saleh (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to identify the reality of knowledge management processes at King Saud University in Riyadh. The study society, which is equal to (521), consists of the faculty and staff for both gender of the College of Business Administration at King Saud University and the descriptive survey method was used. To achieve the objectives of the study, a questionnaire consisting of two parts was used: Part 1: deals with the initial data of the study members. The second part consists of four main axes representing knowledge management processes, and the data was processed using SPSS. One of the most important findings of the researcher is that there is a high degree of agreement among the members of the sample to practice the process of knowledge discovery, where the general arithmetic average (3.60) of 5 (high degree), and that there is high approval among the sample on the practice of storage (3.82) from (5), which is a high degree, and there is a high degree of agreement among the sample members on the practice of knowledge sharing, where the general arithmetic average (3.63) is (5) A high level of approval among the sample members on the practice of using the knowledge, where the general arithmetic mean (3.59) Of (5) a high degree. The most important recommendations made by the researcher are to work on the transparency of knowledge and make it available to employees and beneficiaries at King Saud University, and the need to monitor the rewarding rewards for the employees who provide knowledge achievements to motivate them to spread knowledge, and to facilitate the procedures that hinder the use of knowledge to solve problems accurately and quickly.
Keywords: knowledge management; knowledge discovery process; knowledge storage process; The process of sharing knowledge; the process of using knowledge